(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Waqf in Islam has historically been a vital institution in fulfilling religious needs and social welfare. Its effectiveness in medieval and modern Islam is evident. Yet, this institution is seemingly not without inefficiencies. Agency problem and idle, even dilapidated assets are commonplace, besides inancial constraints and poor human resources are also cited as key impediments. Thus, public trust and contribution are becoming low due to the opacity of the accounting and accountability system. As such, scholars propose the adoption of blockchain technology to mitigate these issues. This paper aims to review the waqf and its types, as well as blockchain technology and its models. The review makes clear that implementation of blockchain technology in managing waqf endowment is pertinent by using a smart contract. The article raises important issues in addition to its caveats pertaining to waqf based on blockchain, which offers solutions in the current problems for its effective implementation for waqf management. This study contributes to the field of waqf endowment as it highlights the use of blockchain technology in managing waqf, which could be useful for Mutawalli (trustee) of waqf towards the sustainability of Islamic social finance.